HUBUNGAN ANTARA LEMAK VISERAL, LINGKAR PERUT DAN RASIO LINGKAR PINGGANG PANGGUL DENGAN KADAR SERUM MAGNESIUM PADA WANITA USIA SUBUR OBESITAS SENTRAL - Widiasih, Esti; SS, Darmono; AK, Nugrohowati (Universitas Diponegoro, 2019)
Background: Obesity is a major public health problem today. Chronic imbalances between energy intake and energy expenditure will eventually cause obesity. Central obesity proved to be more at risk for health problems. Some micronutrients are found to be involved in the development of obesity. Magnesium is found to have a role in the development of obesity. Objective: to analyse the association of serum magnesium with various central obesity parameters such as abdominal circumference (WC), waist-hip ratio (WHR) and the amount of visceral fat in woman of reproductuve age with central obesity based on the hypothesis that obese subjects with hypomagnesemia are more prone to fall in complications of metabolic syndrome. Research method: This is a population-based cross-sectional study. A total of 52 apparently healthy adults woman of reproductive age between 18 and 35 years with central obesity (BMI >25 kg/m2,WC >80cm ),were recruited with prior ethical approval and written informed consent. WC and WHR were measurement using midline, visceral fat using Bioelectrical Impedance Analysis (BIA) and serum magnesium levels from venous blood. Hypothesis testing uses simple correlation and simple linear regression analysis for predictive values. Results: There was a significant negative correlation between Waist circumference (r = -0,473; p = 0,000), WHR (r = -0,476; p = 0,000) and visceral fat (r = -0,628; p = 0,000) with serum magnesium levels. Conclusion: there is a significant correlation between the size of the Waist circumference, WHR and visceral fat (central obesity) to decrease serum magnesium levels. Keywords: waist circumference, WHR, visceral fat, central obesity, serum magnesium ABSTRAK Latar belakang : Obesitas adalah masalah kesehatan masyarakat utama saat ini. Ketidakseimbangan kronis antara asupan energi dan pengeluaran energi pada akhirnya akan menyebabkan obesitas. Obesitas sentral terbukti lebih berisiko pada masalah kesehatan. Beberapa mikronutrien ditemukan terlibat dalam perkembangan obesitas. Magnesium ditemukan memiliki peran dalam perkembangan obesitas. Tujuan: menganalisis hubungan serum magnesium dengan berbagai parameter obesitas sentral seperti lingkar perut (LP), rasio pinggang-panggul (RLPP) dan jumlah lemak viseral pada WUS obesitas sentral berdasarkan hipotesis bahwa subjek obesitas dengan hipomagnesemia lebih rentan jatuh dalam komplikasi sindrom metabolik. Metode penelitian : penelitian korelasional dengan desain cross sectional melibatkan subyek WUS obesitas sentral sebanyak 52 subyek di kota Semarang dari bulan April-Mei 2019 yang memenuhi kriteria inklusi dan eksklusi. Dilakukan pengukuran LP, RLPP, dan lemak viseral menggunakan Bioelectrical Impedance Analysis (BIA) dan kadar serum magnesium dari darah vena. Uji hipotesis menggunakan korelasi sederhana dan analisis regresi linier sederhana untuk nilai prediksi. Hasil: : Terdapat korelasi negatif bermakna antara lingkar perut (r=-0,473; p=0,000), RLPP (r=-0,476; p=0,000) dan lemak viseral (r=-0,628; p=0,000) dengan kadar serum magnesium. Simpulan : terdapat korelasi bermakna antara besarnya lingkar perut, RLPP dan lemak viseral (obesitas sentral) terhadap penurunan kadar serum magnesium. Kata kunci : lingkar perut, RLPP, lemak viseral, obesitas sentral, WUS, serum magnesium